On a Traumatic Cranial Injury from a “Mongol” Burial at Mingachevir (Republic of Azerbaijan) - Kirichenko, Dmitriy; Abdullayev, Anar; Kasamanli, Afqana; Qasimova, Samira (Revista Arheologică, 2026)
The article examines anthropological materials dating to the medieval period, recovered during rescue archaeological excavations (field season of 1950) conducted in the construction zone of the Mingachevir Hydroelectric Power Station at Settlement No. 3. The study focuses on a cranium (No. 1) belonging to a male individual aged over 45 years at the time of death, originating from a so-called “Mongol” burial dated to the late 13th − early 14th centuries. At present, the human cranium is housed in the exhibition of the Museum of Human Anatomy at the Department of Anatomy and Medical Terminology, Azerbaijan Medical University (Baku, Republic of Azerbaijan). The examined cranium is brachycranial and exhibits Mongoloid morphological traits, corresponding to a representative of the Central Asian anthropological type. A traumatic lesion was identified on the left temporal bone: a sharp-force chop wound measuring 4.8 cm in length and approximately 3 mm in width, with a total affected area of 7.5 cm. The absence of healing indicates that the injury is diagnostic of perimortem trauma. The fatal injury was most likely inflicted by a sharp sabre or a long-edged sword. The study incorporates data obtained through modern computed tomography (CT) scanning of the cranium, which confirmed and further refined our conclusions regarding the identi-fied lethal cranial injury of the Mongol warrior. The article also presents comparative data on perimortem trauma from contemporaneous (13th-14th centuries) contexts in the Caucasus, the Middle East, Eastern Europe, and the Volga region, summarized in a consolidated table.